Blowin’ in the wind: mapping the dispersion of metal(loid)s from Atacama mining - Zanetta Colombo, Nicolás; Manzano, Carlos A.; Brombierstäudl, Dagmar; Fleming, Zoë L.; Gayo, Eugenia M.; Rubinos, David A.; Jerez Riveros, Oscar; Valdés, Jorge; Prieto, Manuel; Nüsser, Marcus (GeoHealth, 2024)
The Atacama Desert’s naturally elevated metal(loid)s pose a unique challenge for assessing the environmental impact of mining, particularly for indigenous communities residing in these areas. This study investigates how copper mining influences the dispersion of these elements in the wind-transportable fraction (<75 μm) of surface sediments across an 80 km radius. We employed a multi-pronged approach, utilizing spatial modeling to map element distributions, exponential decay analysis to quantify concentration decline with distance, regime shift modeling to identify dispersion pattern variations, and pollution assessment to evaluate impact. Our results reveal significant mining-driven increases in surface concentrations of copper (Cu), molybdenum (Mo), and arsenic (As). Notably, within the first 20 km, concentrations peaked at 1,016 mg kg⁻1 for Cu, 31 mg kg⁻1 for Mo, and a remarkable 165 mg kg⁻1 for As. Cu and Mo displayed significant dispersion, extending up to 50 km from the source. However, As exhibited the most extensive reach, traveling up to 70 km downwind, highlighting the far-reaching ecological footprint of mining operations. Mineralogical analyses corroborated these findings, identifying mining-related minerals in surface sediments far beyond the immediate mining area. Although pollution indices based on the proposed Local Geochemical Background reveal significant contamination across the study area, establishing accurate pre-industrial baseline values is essential for a more reliable assessment. This study challenges the concept of “natural pollution” by demonstrating that human activities exacerbate baseline metal(loid)s levels. Expanding monitoring protocols is imperative to comprehensively assess the combined effects of multiple emission sources, including mining and natural processes, in safeguarding environmental and human health for future generations.
Gesehen am 07.10.2024